Fecal shedding level of Haemonchus contortus is associated with gastrointestinal bacterial microbial composition in naturally infected sheep - Jeferson Vidart Ramos; Verônica Rocha Merched; Laura Dias da Silva Ribeiro; Guilherme Neves Lima Rattmann; Renan Eugênio Araújo Piraine; Fabio Pereira Leivas Leite (Revista Brasileira de Parasitologia Veterinária)
Abstract A complex interaction of gastrointestinal parasites with sheep hosts may involve bacteria communities, parasite genera, parasitic genes, and biological pathways. Haemonchus contortus presents a global challenge for ruminants, and the bacterial community can influence sheep's resistance and susceptibility to these parasites. Thus, a better understanding of this complex interaction could contribute to the development of a new approach to parasite control. This study evaluated the bacterial community of Corriedale sheep naturally infected with H. contortus based on the fecal egg counts over ten months and then classified as having low (LC), intermediate (IC), or high (HC). Stool samples were collected monthly for egg counts (EPG), and 16S rRNA gene sequencing was performed on five animals from each group. The average EPG was 2,635 ± 105 for HC, 845 ± 129 for IC, and 110 ± 70 for LC, with a significant difference (p = 0.0001). Firmicutes, Proteobacteria, and Spirochaetes were more abundant in the HC group. 102 bacterial genera showed significant differences between the LC and HC groups. Beta diversity was statistically different (p<0.005) for HC compared with the other two groups; also, different communities were found between LC and HC. Sediminispirochaeta, Oribacterium, Alloprevotella, Prevotellaceae_UCG-001, Prevotellaceae_UCG-003, Ruminiclostridium_6 and Ruminococcus_1were significant more abundant in LC, and IC group. Acetobacter and Methanocorpusculum had a significant reduction in the LC group. Thus, bacterial genera related to low methane emission and food efficiency were significantly present in the LC group. Therefore, a better understanding of the role of host-bacterial community-parasite interaction could contribute to improving parasite control management.